Respuesta :

Answer:

y = mnp/(m + n)

Step-by-step explanation:

I assume that both capital y and small case y are meant to be the same variable. If not, let me know, and I'll solve it again for small case y.

y/m + y/n = p

Factor y out on the left side.

y(1/m + 1/n) = p

y = p/(1/m + 1/n)

Multiply the right side by (mn)/(mn).

y = pmn/[(1/m + 1/n)mn]

y = pmn/(n + m)

y = mnp/(m + n)

Solve for y:

y/m + y/n = p

yn + ym = pmn

y = pmn / n + m

Hope this helps :)

please give brainliest

ACCESS MORE